Synthesis Of Silver Nanoparticles Using Extract Of Neem Leaf And Triphala And Evaluation Of Their Antimicrobial Activities - ASMITA J. GAVHANE; P. PADMANABHAN; SURESH P. KAMBLE; SURESH N. JANGLE (International Journal of Pharma and Bio Sciences, 2012)
Silver nanoparticles were synthesized using extracts of Neem (Azadirachta indica) leaves and Triphala-a well known herbal mixture, used widely in treatment of various ailments. The characteristics of silver nanoparticles were studied using NTA, TEM and EDX. The EDX spectrum of the silver nanoparticles confirmed the presence of elemental silver signal. NTA measurements showed that the average size of silver nanoparticles synthesized using Neem leaves extract were 43nm and 59nm for silver nanoparticles synthesized by Triphala. TEM analysis showed that the silver nanoparticles were predominantly spherical in nature. It was found that the growth of gentamycin and ampicillin resistant K. pneuomoniae was inhibited by both Neem and Triphala synthesized silver nanoparticles. Similar observations were noted for gentamicin and piperacillin resistant S. typhi. Fluconazole resistant C. albicans were found to be sensitive to silver nanoparticles. Growth of multiple drug resistant E.coli was inhibited by silver nanoparticles and this effect was augmented by synergistic action of gentamycin and the silver nanoparticles synthesized by aqueous extract of Neem and Triphala.